Differential Effect of Single Leg Tuck Jump With Depth Jump On Increasing Limb Muscle Power In Futsal Players at SMAN 15 Makassar - Muh. Fathurrahman Wahid; Muh. Thahir; Aco Tang (UNIVERSITAS NEGERI MAKASSAR, 2022)
This study aims to determine the difference in the effect of Single Leg Tuck Jump and Depth Jump on Increasing Limb Muscle Explosive Power in Futsal Players at SMA Negeri 15 Makassar with a sample of 18 people who fit the inclusion criteria, randomized into 2 groups, namely treatment group I given Single Leg Tuck Jump and treatment group II given Depth Jump. This study uses a vertical jump test to measure the explosive power of the leg muscles. The type of research used by the researcher is experimental research using a Quasi Experiment design. In this study, the pre-test-post-test two-group design method was used. Based on the analysis of the paired-sample t-test in the treatment data group I, the value of p = 0.000 was obtained. Treatment data group II obtained a p-value = 0.000. The data above for treatment groups I and II show that there is a significant effect of Single Leg Tuck Jump and Depth Jump. Then, based on the independent t-test, the p-value = 0.003, which means that there is a significant difference between treatment group I and treatment group II. This study concludes that the provision of Single Leg Tuck Jump exercises is more effective than Depth Jump exercises to increase leg muscle explosive power in futsal players.